Phyto-oxylipin mediated plant immune response to colonization and infection in the soybean-Phytophthora sojae pathosystem - Adigun, Oludoyin Adeseun; Pham, Thu Huong; Grapov, Dmitry; Nadeem, Muhammad; Jewell, Linda Elizabeth; Cheema, Mumtaz; Galagedara, Lakshman; Thomas, Raymond (Frontiers in Plant Science, 2023)
Food security is a major challenge to sustainably supply food to meet the demands of the ever-growing global population. Crop loss due to pathogens is a major concern to overcoming this global food security challenge. Soybean root and stem rot caused by Phytophthora sojae results in approximately 2B $US crop loss annually. Lipid mediated plant immunity is a very attractive target for developing long term resistance in many plant disease pathosystem. However, little is known about the phyto-oxylipin’s role in the successful strategies used by tolerant soybean cultivar to mitigate Phytophthora sojae infection. We used scanning electron microscopy to observe the alterations in root morphology and a targeted lipidomics approach using high resolution accurate mass tandem mass spectrometry to assess phyto-oxylipin anabolism at 48 h, 72 h and 96 h post infection. We observed the presence of biogenic crystals and reinforced epidermal walls in the tolerant cultivar suggests a mechanism for disease tolerance when compared with susceptible cultivar. Similarly, the unique biomarkers of oxylipin mediated plant immunity [10(E),12(Z)-13S-hydroxy-9(Z),11(E),15(Z)-octadecatrienoic acid, (Z)-12,13-dihydroxyoctadec-9-enoic acid, (9Z,11E)-13-Oxo-9,11-octadecadienoic acid, 15(Z)-9-oxo-octadecatrienoic acid, 10(E),12(E)-9-hydroperoxyoctadeca-10,12-dienoic acid, 12-oxophytodienoic acid and (12Z,15Z)-9, 10-dihydroxyoctadeca-12,15-dienoic acid] generated from intact oxidized lipid precursors in a tolerant soybean cultivar relative to infected susceptible cultivar and non-inoculated controls at 48 h, 72 h and 96 h post infection by Phytophthora sojae. While microbial origin oxylipins, 12S-hydroperoxy-5(Z),8(Z),10(E),14(Z)-eicosatetraenoic acid and (4Z,7Z,10Z,13Z)-15-[3-[(Z)-pent-2-enyl]oxiran-2-yl]pentadeca-4,7,10,13-tetraenoic acid were upregulated only in infected susceptible cultivar but downregulated in infected tolerant cultivar. These unique biomarkers maybe used in tolerant cultivar as a mechanism for disease tolerance. This study demonstrated novel evidence for phyto-oxylipin metabolism in soybean cultivars during pathogen infection and this evidence may be a potential application in further elucidation of the role of phyto-oxylipin anabolism in soybean tolerance to Phytophthora sojae infectionn